Core nucleus dynamics in Λ hypernuclei - Qamar Nasir, Usmani; Bodmer, A. R.; Zaliman, Sauli, Prof. Madya (World Scientific Publishing Co, 2010)
Link to publisher's homepage at http://www.worldscinet.com/